2020
DOI: 10.3390/ma13122717
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Characterisation and Identification of the Mechanical and Functional Properties of a New PMMA-ZnO Composite

Abstract: In this research work, we synthesised poly(methyl methacrylate) (PMMA) enriched with 2 wt.% zinc oxide nanoparticles (ZnO) through conventional heat polymerisation and characterised its microstructure. It was found that the distribution of ZnO nanoparticles was homogeneous through the volume of the PMMA. The mechanical testing of the PMMA-ZnO composite primarily included the determination of the compressive properties on real dentures, while density measurements were performed using a pycnometer. The testing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In addition to the influence of density on the porosity of PMMA, a higher density of the material means a heavier denture base. It is clear that dentures should be as light as possible, which is especially important for upper dentures [ 19 ]. In this respect, the similar density of PMMA and PMMA/AuNPs could be considered as a satisfactory characteristic of the modified PMMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the influence of density on the porosity of PMMA, a higher density of the material means a heavier denture base. It is clear that dentures should be as light as possible, which is especially important for upper dentures [ 19 ]. In this respect, the similar density of PMMA and PMMA/AuNPs could be considered as a satisfactory characteristic of the modified PMMA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proven that silanized glass fiber improves flexural strength and biocompatibility [ 16 , 17 ], while decreasing porosity and the adherence of Candida albicans [ 18 ]. PMMA with incorporated zinc oxide nanoparticles has been shown to be biocompatible and has improved fractural strength [ 19 ]. Furthermore, silver nanoparticles incorporated into PMMA increase the compressive strength, viscoelastic strength and thermal conductivity of PMMA [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Alghsham et al (2019) demonstrated that exposure to ZnO-NWs may induce distinct inflammatory responses through phagocytic uptake. Rudolf et al (2020) concluded that the PMMA-ZnO-NPs did not induce direct or indirect cytotoxic effects in L929 cell cultures.…”
Section: Introductionmentioning
confidence: 96%
“…biofilms infections to improve clinical outcomes. Studies have revealed that dental base resin poly(methyl-methacrylate) (PMMA) has antimicrobial activity and improves mechanical and physical properties when metal nanoparticles (NPs) and oxide-metal-NPs were incorporated in monomers ( Li et al, 2016 , Cierech et al, 2016a De Matteis et al, 2019 , Rudolf et al, 2020 ). Nanowires (NWs) have the advantage of reinforcing the matrix due to winding of the polymer chains, increasing their dimensional stability and mechanical properties ( Rajaka et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation